C&T NO MEIO RURAL: A divulgação de Ciência e Tecnologia no programa televisivo Caminhos da Roça - Rosa, Caroline Petian Pimenta Bono (2008)
This research explores the speech of a Brazilian and regional open TV program in order to identify which language was used to broach issues in Science and Technology. The corpus is made of an extract based on the 2006 TV program broadcast Caminhos da Roça created and broadcasted since 2002 by EPTV Ribeirão (Empresas Pioneiras de Televisão) a Rede Globo affiliate in Ribeirão Preto/SP. The proposal was to analyse what is concerned to the form, language and journalistic s issues and subjects that specifically deal with Science and/or Technology s issues directed to agrobusiness and had also shown any contact between the researcher and the farm citizen. This qualitative nature study has used the methodology of Speech Analysis on the French Line (SA) and has identified S&T as a quite present subject in Caminhos da Roça. It has also been testified that though there is much dissemination S&T there is no study pattern of these issues and the approach varies in each episode; besides the fact that science is shown as a way of technology directed to the field. The used language by Caminhos da Roça deals with Science and Technology issues and it is mostly clear and simplified, moreover, the most present speech is defined as a mixture of technologic, informative and pedagogic.(AU)